Municipal Solid Waste Management in Amazonas, Brazil (Research, Society and Development, 2020)
The aim of this study was to analyze the solid waste management system in the amazonian cities of Silves and Itapiranga. Nine sustainability indicators previously established through bibliographic studies were used, being classified into five levels of criteria. Technical visits were carried out in the cities, contemplating the administrative areas where semi-structured interviews with the municipal managers were applied. At the final disposal site, the Waste Landfill Quality Index (IQR-Dichtes) was applied. Both cities had a critical stage in the Environmental Impacts indicator and the other indicators showed an unfavorable stage. However, Silves managed to present a regular result in the Social Extension indicator, while Itapiranga presented a regular result in the Service Provision indicator. The cities have demonstrated that they have an inefficient solid waste management system that does not include what is determined by national and state solid waste policies, thus requiring improvements at each stage of management.